Does Socioeconomic and Environmental Factors Exacerbate Undernourishment in Asia and Africa? - Azhar, Neng Zulfa; Pratama, Dito Alif; Lapasa, Amanca Pamalina (Jurnal Ekonomi Pembangunan, 2025)
This study investigates the impact of socioeconomic and environmental factors on undernourishment, across seven selected countries in Asia and Africa from 2001 to 2020. Employing a fixed-effects panel regression, we analyze the impact of GDP per capita, female employment in agriculture, electricity access, greenhouse gas emissions, and foreign direct investment on the incidence of undernourishment. Our findings indicate that higher GDP per capita, greater female participation in agricultural labor, and improved electricity access are associated with significant reductions in undernourishment. Conversely, elevated greenhouse gas emissions and increased foreign direct investment appear to exacerbate undernourishment. These results underscore the critical need for policymakers to prioritize investments in sustainable agricultural practices, emphasizing low-emission technologies that enhance both efficiency and product quality. Furthermore, expanding electrification and empowering women in agriculture are crucial strategies for strengthening household food security by increasing food availability and diversity. This study provides an integrated perspective on the complex challenge of undernourishment, highlighting the dynamic interplay between economic and environmental policies.